Desenvolvendo personas para o mercado de jogos casuais para download - Breyer, Felipe; Moura, Luiz José; Cavalcanti, Giulia; Filho, Vicente; Caraciolo, Marco Túlio (InfoDesign, 2009)
The article presents the results obtained by the application of the Persona technique using social networks as research tool, in order to turn possible the acquisition of data of the target public in a remote way. The information described here constitute the results of the first step of the FunFactory research project that has the objective of optimize the game development process for casual players. During the research phase for the creation of the Persona, it was registered the users’ data samples according to the casual players profile pointed by International Game Developers Association using the MySpace network, including demographic data and users preferences among different medias. After the analysis of the data, the project created two Personas for Manifesto Game Studio, those will also serve as primary and secondary requirements for the next step of the process when this material could be utilized for the conception of the game.